Duration of hemodynamic effects of crystalloids in patients with circulatory shock after initial resuscitation - Nunes, Thieme Souza Oliveira [UNIFESP] (2014)
Background: in the later stages of circulatory shock, monitoring should help to avoid fluid overload. in this setting, volume expansion is ideally indicated only for patients in whom the cardiac index (CI) is expected to increase. Crystalloids are usually the choice for fluid replacement. As previous studies evaluating the hemodynamic effect of crystalloids have not distinguished responders from non-responders, the present study was designed to evaluate the duration of the hemodynamic effects of crystalloids according to the fluid responsiveness status.Methods: This is a prospective observational study conducted after the initial resuscitation phase of circulatory shock (>6 h vasopressor use). Critically ill, sedated adult patients monitored with a pulmonary artery catheter who received a fluid challenge with crystalloids (500 mL infused over 30 min) were included. Hemodynamic variables were measured at baseline (T0) and at 30 min (T1), 60 min (T2), and 90 min (T3) after a fluid bolus, totaling 90 min of observation. the patients were analyzed according to their fluid responsiveness status (responders with CI increase >15% and non-responders <= 15% at T1). the data were analyzed by repeated measures of analysis of variance.Results: Twenty patients were included, 14 of whom had septic shock. Overall, volume expansion significantly increased the CI: 3.03 +/- 0.64 L/min/m(2) to 3.58 +/- 0.66 L/min/m(2) (p < 0.05). From this period, there was a progressive decrease: 3.23 +/- 0.65 L/min/m(2) (p < 0.05, T2 versus T1) and 3.12 +/- 0.64 L/min/m(2) (p < 0.05, period T3 versus T1). Similar behavior was observed in responders (13 patients), 2.84 +/- 0.61 L/min/m(2) to 3.57 +/- 0.65 L/min/m(2) (p < 0.05) with volume expansion, followed by a decrease, 3.19 +/- 0.69 L/min/m(2) (p < 0.05, T2 versus T1) and 3.06 +/- 0.70 L/min/m(2) (p < 0.05, T3 versus T1). Blood pressure and cardiac filling pressures also decreased significantly after T1 with similar findings in both responders and non-responders.Conclusions: the results suggest that volume expansion with crystalloids in patients with circulatory shock after the initial resuscitation has limited success, even in responders.